A Revolução Farroupilha na literatura brasileira: a conversão ficcional de personagens históricos em obras literárias nacionais - Alves, Evandro Fantoni Rodrigues (2022)
This thesis deals with the process of fictional conversion of historical characters from the Farroupilha Revolution in four works of Brazilian literature, published in different periods between the second half of the 19th century and the first half of the 21st century. They are: O gaúcho (1870), by José de Alencar; Os amores de Canabarro (1933), by Othelo Rosa; Os varões assinalados (1985), by Tabajara Ruas; and A casa das sete mulheres (2002), by Letícia Wierzchowski. Our objective is to understand how certain historical characters are presented in literary works from different periods, and how these historical fiction texts approach the theoretical formulations of György Lukács about the traditional historical novel, or Linda Hutcheon’s about the historiographic metafiction. For that, our methodology was to choose four important historical episodes of the Farroupilha Revolution – the taking of Porto Alegre; the proclamation of the Rio-Grandense Republic; the Julian Republic; and the Ponche Verde peace – and to verify to how they approach or distance themselves from the theoretical constructs that underlie our research. At the end of these analyzes we will verify if our thesis - which revolves around the idea that the limits between the traditional historical novel and the historiographic metafiction become increasingly diffuse, insofar as literary works of a historical nature have a double approach to the two theories – can be confirmed or refuted by the literary analyzes carried out throughout the present study